A Case study on the inventory system of Manila Adventist Medical Center - Escobar, Cristine Marie D.; Lamadrid, Maria Inez R.; Villanueva, Raquel D. (Department of Industrial Engineering and Operations Research College of Engineering, University of the Philippines Diliman, Quezon City, 2004)
Manila Adventist Medical Center (MAMC) is a private institution owned and operated by the Seventh-day Adventist Church. Since it is a non-profit hospital, it has to minimize its expenses to sustain its everyday operations while maintaining a high service level to patients. An area that is incurring large percentage of hospital expenditures is on maintaining hospital supply in inventory. With this, an inventory management study is done on MAMC to address the problems relating to inventory. This study focused on the current inventory system and other inventory related problems of the two products. (Macro and Soluset) identified in the Pareto Analysis. Stream Diagnostic Diagram was used to identify the two (2) main problems. These are Q and R in Purchasing Department do not match its level of demand and Q and R in User Department do not match its level of demand since they both have the most number of outgoing arrows. The following areas for improvement were investigated in the study: 1. Q and R for both Purchasing and Pharmacy - These parameters determine occurrence of stockout or excess inventory; and 2. Forecasting for Purchasing - this would determine expected demand that would aid in a more appropriate inventory system. Several forecasting techniques were used to determine which is best to predict future demands for the two supplies in focus considering the seasonality pattern of the demands.For the plot of tracking signals for Macro with Weighted Moving Average 0.7, the points generally cluster around 0, which would imply that forecasts are not biased. For the plot of tracking signals for Soluset with Simple Moving Average n=6, an upward and downward trend can be observed. Although the % differences of the forecasted values with the current demands are generally large, these account large variations in fluctuation. Nevertheless, the forecasted values are valid and good estimates of expected demand for 2004. The analysis of the current inventory system, showed percentage of stockout costs to total costs for Soluset and Macro respectively is 1.32% and 5.24%. Another prominent result is the high holding costs incurred on both supplies. The % holding cost to total cost for Soluset is 74.85% and 61.23% for Macro. It is ideal to balance these two parameters to bring total cost to the minimum. The Q and P system alternatives were investigated and evaluated at a 95% service level as a Purchasing Department Policy. Comparing the two models used as alternatives -- the Q system and P system, it can be concluded that Q system is better than the P system and the existing system. The alternative that best met the cost and stockout considerations is the Economic Order Quantity (EOQ) or Q System. This is the recommended inventory management system that will be expected to give savings of 71.63% and 56.44%, respectively for Soluset and Macro, respectively. These percentages translate to savings of P628,358.86 for Soluset and P190,020.25 for Macro in terms of holding, ordering and stockout costs. Implementation plans for the recommended inventory system were provided to initially determine how this study can be realized and its benefits be experienced by MAMC. Since the study is bounded with certain limitation, areas for further studies were proposed to tackle more improvements for MAMC.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: Manila Adventist Medical Center; Hospitals; Production engineering